TEACHERS’ VIEWS ON ACADEMIC WRITING ASSIGNMENTS GENERATED BY ARTIFICIAL INTELLIGENCE: HOW DO THEY AFFECT THE TEACHING METHODS IN HIGHER EDUCATION INSTITUTIONS - Shaikenova Dana (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Generative artificial intelligence technologies in higher education have rapidly influenced academic writing, raising concerns about academic and linguistic integrity. This transformation in foreign language teaching creates a critical conflict between the effectiveness of technology and the ability of students to learn through real means. To answer this new question, this study examines the attitude of teachers of “Academic Writing” and “English for Academic Purposes” at two Kazakhstani universities towards tasks generated by artificial intelligence, with an emphasis on pedagogical responses and linguistic integrity. In the course of the study, conducted using mixed methods, 15 teachers were interviewed. Descriptive statistics were used to identify the validity, evaluation, and institutional support of quantitative data. The transcripts of the interviews were examined during the thematic analysis. The results show that most teachers have worked with AI-generated assignments that are well-written grammatically but lack creativity, critical thinking, or student voice. Excessive use of AI also worries teachers about critical thinking and reflective learning in students. Teachers use multimodal assessments, oral defenses, reflective comments, and drafts to emphasize the importance of the learning process rather than the results. The study highlights the lack of institutional norms regarding artificial intelligence in assignments and shows how foreign language teachers combine technological innovation and academic integrity.